Chemical composition of Pennisetum purpureum cv.. Cuba CT-115 used as biomass bank - Fortes, Dayleni; Herrera, Rafael Segundo; Garc?a, Manuel; Cruz, Ana Mar?a; Romero, Aida (Cuban Journal of Agricultural Science, 2012)
A completely random sampling design was used to study the chemical composition of CT-115 used as biomass bank. The treatments corresponded with the re-growth ages of the pasture from the moment the animals went out to the paddock (zero time) to completing each growth cycle, according to the technology of biomass bank. In all the cycles, the re-growth age diminished the CP value (P < 0.001) and the cell content (P < 0.01) in the basal tillers as in the residue. The higher protein values were found in the leaves of the basal tillers and the residue (P < 0.001), with 14.3 % and 11.9 % respectively, at 15 d in cycle one. The cell wall increased (P < 0.01) with age in all cycles. The leaves had lower values than the stems. The highest values were, generally, in the residue stems (84.07 %), at 105 d of re-growth for cycle four. The cellulose and lignin contents increased with age in most of the cycles, with maximum values in the leaves of 38.8 % and 7.9 %, respectively. The lignin values were inferior in leaves and stems of the basal tillers. The results of this study allow concluding that the cell wall, cellulose and lignin increased with the re-growth age. The CP and the cell content reduced similarly in the rest of the pastures. However, these indicators in the leaves of CT-115 get to the 105 d with an acceptable quality for cattle. Due to the leaves quality in this variety of Pennisetum, grazing with a high defoliation index up to the height desired by the animal is recommended and, therefore, a higher productivity would be achieved. Key words: Pennisetum purpureum cv.. Cuba CT-115, chemical composition, biomass bank.